Governing a therapeutic community prison in an age of managerialism. Issue 1 (9th April 2018) - Bennett, Jamie
Abstract : Purpose: Recent ethnographic research has examined the forces that shape the working lives of prison managers, in particular, the growth of managerialism, pushing in from the outside and the deeply rooted local cultures that exist within. The purpose of this paper is to reconsider the interplay of these forces in the context of a therapeutic community (TC) prison. Design/methodology/approach: This paper draws upon ethnographic research conducted in two prisons and expands this using an autoethnographic approach to examine the experience of governing a TC prison. Findings: The original study described how the dynamic interaction of globalised change and local culture created gave rise to "prison managerialism". This notion reflects the negotiation between the global managerialism and local occupational culture. This concept is equally relevant in a TC prison, albeit it exists in an altered form reflecting the distinct characteristics of the local culture. Research limitations/implications: The approach builds upon an ethnographic study, expanding this through autoethnography. This inevitably limits the scope and perspective as it is looking at a specific context. It nevertheless highlights the distinctive challenges of managing a TC prison. Practical implications: The work has implications for the management of TC prisons in practice, including human resource management such as recruitment, selection, appraisal and development of those managers. Originality/value: The paper applies and revisits a recent in-depth study of prison managers, re-imagining and revising this to reflect the distinct context of managing a TC prison.